Spitsbergen Literature Lobby - Jones, Mary Katherine (Nordlit, 2014)
The Spitsbergen (Svalbard) Question became an international political issue regarding the terra nullius status of the Arctic region in the light of growing commercial enterprise undertaken from 1898 onwards. The Spitsbergen Commission set up by the Peace Conference in Paris to resolve this question in the aftermath of the Great War awarded sovereignty to Norway. Elen C. Singh’s concept of the Spitsbergen Literature Lobby illustrates behind-the-scenes activity intent on resolving Spitsbergen sovereignty in favour of one particular nation, and/or securing the commercial interests of several nations. Documents analysed in this article include the initial Norwegian Government submission to the Peace Conference and the contemporaneous diary of one of its main compilers; Spitsbergen Literature Lobby texts cited by Singh, and other strategic texts published 1906-1919; and selected Spitsbergen texts published in the light of Norwegian sovereignty. Subject matter comprised Spitsbergen summaries, history (including Spitsbergen bibliographies), cartography, legal/political issues and commercial issues. The specific and general influence of the lobby and the expertise of its constituent authors is examined, as are their individual and collaborative literary efforts, as well as the rationale behind the selection of strategic texts and a summary of their time-scale, location and language of publication.